2009
DOI: 10.1177/1079063209342073
|View full text |Cite
|
Sign up to set email alerts
|

Penile-Response Profiles of Sexual Aggressors During Phallometric Testing

Abstract: This study analyzes sexual-preference profiles in a sample of 420 sexual aggressors who exhibited a valid profile during their initial phallometric assessment. The sexual stimuli used in the process were audiotapes describing sexual-offending scenarios. Two types of sexual stimuli sets were used: one developed for sexual aggressors against women and a second developed for sexual aggressors against children. Penile responses were recorded during stimulus presentation using a mercury-in-rubber strain gauge. Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
3
25
0
1
Order By: Relevance
“…In these studies, men who molest girls and men who molest boys respond to the gender of the child in a way that matches their preference for the gender of adults. However, even within groups of men who molest girls, there is a considerable diversity (Barbaree & Marshall, 1989;Bickley & Beech, 2001;Michaud & Proulx, 2009). In addition, it has been demonstrated that child molesters who target boys are more likely to seek out victims who are unknown to them, and these offenders appear to be at greater risk to reoffend than are those who molest girls (Grubin & Kennedy, 1991;Hanson, Steffy, & Gauthier, 1993).…”
Section: Prior and Current Categoriesmentioning
confidence: 98%
“…In these studies, men who molest girls and men who molest boys respond to the gender of the child in a way that matches their preference for the gender of adults. However, even within groups of men who molest girls, there is a considerable diversity (Barbaree & Marshall, 1989;Bickley & Beech, 2001;Michaud & Proulx, 2009). In addition, it has been demonstrated that child molesters who target boys are more likely to seek out victims who are unknown to them, and these offenders appear to be at greater risk to reoffend than are those who molest girls (Grubin & Kennedy, 1991;Hanson, Steffy, & Gauthier, 1993).…”
Section: Prior and Current Categoriesmentioning
confidence: 98%
“…More recently Michaud and Proulx [11] eliminated data from 264 potential participants (out of an original sample of 745) because they were determined to be low responders or non-responders, and Lykins et al noted that previous studies in their lab had excluded from analysis all subjects who failed to meet a criterion threshold of arousal [26]. In fact it was "to mitigate the problem of low responses in phallometric studies" that Bradford et al undertook research examining the effect of prescribing 50 mg sildenafil (Viagra) to phallometric testing participants [20].…”
Section: Introductionmentioning
confidence: 99%
“…There are nonetheless a great many researchers and clinicians who recognize the worth of this procedure on a number of dimensions and advocate for its use in both research and clinical settings [8][9][10][11][12][13]. The differing opinions which have been ventured with regard to the value of phallometric assessment should not be viewed with any discomfort, however, for as so eloquently expressed about a different contentious issue [14]"It is the nature of a maturing field of study that opposing views are expressed and, indeed, the clear articulation of contrary opinion is the lifeblood of progress in science.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are observed which evaluate different types of sex offenders, including child molesters (Marshall & Marshall, in press;Michaud & Proulx, 2009), rapists Looman and Marshall (2005), sexual sadists (Marshall & Yates, 2004;Proulx, Blais, & Beauregard, 2006) and exhibitionists Kolářský and Madlafousek (1983). Other studies have measured the effect of substance use on sexual response (George et al, 2006;Harte, 2014),distractions to sexual stimuli Anderson and Hamilton (2014), cognitive mechanisms linked to arousal Both, Laan, and Everaerd (2011) or implications of arousal in condom use Janssen et al (2014).…”
Section: Introductionmentioning
confidence: 99%